2020
DOI: 10.1021/acs.inorgchem.0c02053
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Thermoinduced Metal-to-Metal Electron Transfer and ON/OFF Photoswitching in a Molecular [Fe2Co2] Square Complex

Abstract: A cyanide-bridged [Fe 2 Co 2 ] molecular square complex, {[Fe(Tp)(CN) 3 ] 2 [Co(L) 2 ] 2 }(BF 4 ) 2 •2CH 3 CN•6H 2 O [1;Tp = hydrotris(pyrazol-1-yl)borate and L = bis(1-ethyl-1Himidazol-2-yl)ketone], has been synthesized and characterized fully by single-crystal X-ray diffraction, (photo)magnetic measurements, optical reflectivity, and other physical measurements. 1 exhibits a two-step metal-to-metal electron-transfer (MMET)induced spin transition accompanied by thermal hysteresis (T 1/2 ↑ = 332 and 407 K and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 44 publications
4
55
1
Order By: Relevance
“…[15][16][17] Subsequently, a wide variety of multinuclear molecular PBAs with CTIST character was synthesized. [18][19][20][21][22][23][24][25][26][27][28][29] Apart from larger PBA units and network systems, 30 the field also evolved towards the smallest unit cell, the dinuclear [FeCo] PBA. 31,32 The first dinuclear PBA presented by Bernhardt et al, [33][34][35] however, showed neither thermal-nor photo-induced CTIST.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Subsequently, a wide variety of multinuclear molecular PBAs with CTIST character was synthesized. [18][19][20][21][22][23][24][25][26][27][28][29] Apart from larger PBA units and network systems, 30 the field also evolved towards the smallest unit cell, the dinuclear [FeCo] PBA. 31,32 The first dinuclear PBA presented by Bernhardt et al, [33][34][35] however, showed neither thermal-nor photo-induced CTIST.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Alternatively, the N-donor cyanidometalloligand can be used to build polymetallic switchable species, such as tetranuclear square complexes, [Fe( R Tp)(-CN)]2[M'( R bik)2]2, where R Tp is a tris(pyrazo-1-yl)borate ligand and M' = Fe, Co. [16][17][18] In these cases, when a Co ion occupies the {M'( R bik)2(N-)2} site, reversible metal-metal electron transfer through the cyanido bridge coupled to a spin transition on the {Co( R bik)2(N-)2} site can also be responsible for the magnetic bistability. 19,20 We showed for example that the magnetization could be repeatedly switched on and off in a cyanido-bridged Fe2Co2 square complex. 21 We also demonstrated that pressure could convert a paramagnetic Fe2Co2 complex into a bistable magnetic switch with bistability at room temperature.…”
Section: Introductionmentioning
confidence: 97%
“…3,4 The Fe II LS −CN−Co III LS linkage in [FeCo] PBAs exhibits metal-to-metal electron transfer (MMET) from Fe II LS to Co III LS via a cyanide bridge, which converts the diamagnetic (Fe II LS −CN−Co III LS ) state into the paramagnetic (Fe III LS −CN−Co II HS ) state upon varying the temperature or by light irradiation at low temperature. 8,17 From the last two decades, researchers are following the rational way of synthesizing molecular magnetic and photoresponsive materials via judiciously chosen cyanide building blocks, using various capping ligands, mainly the scorpionate-type poly(pyrazolyl)borate ligands. 3,4 Various [FeCo] molecular architectures have been synthesized following this strategy with exciting properties, for example, single-molecule magnets (SMMs), 18,19 single-chain magnets (SCMs), 20−25 thermoand/or photoinduced MMET, 3,4 spin-crossover systems, 26,27 etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The average Co−N bond distance lies in the range between Co II HS (∼2.1 Å) and Co III LS (∼1.9 Å). 8,17,39,40 For complex The modest change in the bond distance of 2 can be explained as the steric effect between methyl groups of the Tp* ligand and the ethyl group of the bik* ligand, which acts to prevent each group from approaching the other while the complex is cooled to 120 K. This can be justified from the intramolecular centroid distances between the pyrazole ring of Tp* and the closest imidazole ring of bik (1), bik* (2), or vbik (3) ligands. For complexes 1 and 3, while the temperature is decreased, the intramolecular centroid distances decrease, whereas for complex 2 this distance remains almost the same (Figure S6 and Table S7).…”
Section: ■ Introductionmentioning
confidence: 99%